Molecular docking studies of Triphala with catalytic portion of HMG-CoA reductase enzyme - Prasoborn Rinthong; Pawitra Pulbutr; Chawannuch Mudjupa (Shahrekord University of Medical Sciences, 2023)
Introduction: Triphala, consisting of three fruits, Phyllanthus emblica L. (Phyllanthaceae), Terminalia bellirica (Gaertn.) Roxb. (Combretaceae), and T. chebula Retz, is a well-recognized Ayurvedic herbal formulation, used for various therapeutic purposes, including the treatment of dyslipidemia. Inhibitory activity against 3‑hydroxy‑3‑methylglutaryl‑coenzyme A (HMG‑CoA) reductase, a rate-limiting enzyme in the endogenous cholesterol synthesis pathway, is an essential target for the management of hypercholesterolemia. This in silico study aimed to investigate the HMG-CoA reductase inhibitory activity of the phytochemical compounds derived from Triphala formulation by employing molecular docking analysis. Methods: Ten phytochemical constituents of Triphala formulation were selectively used for docking study by using the HMG-CoA reductase template (PDB: 1HWK). Docking analysis was performed using AutoDock 4.2. The candidates were ranked by the binding energy parameters. Results: From the docking studies, the phytochemical compounds with HMG-CoA reductase inhibition could be classified into 4 groups, including phytosterols, polyphenols, tannins, and flavonoids. Beta-sitosterol exhibited the highest binding affinity to HMG-CoA reductase with a binding energy of -7.75 kcal/mol. Conclusion: These 10 phytochemical compounds in Triphala potentially exert their cholesterol-lowering effects via inhibition against HMG-CoA reductase. Nonetheless, further in vitro and in vivo experiments should be conducted subsequently to confirm this finding.